Augmented mast cell infiltration and microvessel density in prostate cancer - Stawerski, Paweł; Wagrowska-Danilewicz, Małgorzata; Stasikowska-Kanicka, Olga; Tuka, Elżbieta; Danilewicz, Marian (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : Recent investigations have taken into account the role of mast cells in prostate cancer formation, analyzing their dual functions (as tumour growth promoters and tumour growth inhibitors). The aim of our study was to compare mast cell infiltration and microvessel density in prostate cancer and in benign prostate hyperplasia. We also attempted to find possible relationships among mast cell infiltration and microvessel density, Gleason score, as well as serum levels of prostate-specific antigen (PSA). Material and methods : The investigation was confined to evaluations of material from prostate needle biopsies, carried out in 26 patients with prostate cancer, and of 14 specimens diagnosed as benign hyperplasia. The numbers of tryptase positive mast cells and CD34 positive vessels were determined using a computer image analysis system. In the patients with prostate cancer, both mast cell infiltrates and microvessel density were significantly increased, as compared to the control patients. Results : Significant positive correlations were identified between the mean numbers of mast cells and microvessel densities, both in the prostate cancer group and in the control group. Moreover, significant positive correlations were observed between Gleason score on one hand and the number of mast cells and microvessel density on the other. The correlations between PSA serum levels and both mast cell infiltration and microvessel density were positive, but not in a statistically significant way. Conclusions : The reported investigations may support the assumption of mast cell promoter function in prostate cancer development, whereas no evidence was found for their opposite